2014
DOI: 10.5152/tftrd.2014.76735
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Physical Medicine and Rehabilitation Strategies for Patients with Cervical Radiculopathy Due to Disc Herniation

Abstract: ÖzetSinir kökü kompresyonu veya irritasyonu nedeni ile motor, duyusal veya refleks değişikliklerin eşlik ettiği, kola yayılan ağrı ile beraber boyun ağrısının varlığı ise servikal radikülopati olarak tanımlanır. Bu derlemenin amacı, disk hernisi sonucu oluşan servikal radikülopatili hastaların tedavisinde fiziksel tıp ve rehabilitasyon yaklaşımlarının etkinliği ile ilgili son gelişmeleri bütünsel bir yaklaşımla gözden geçirmek ve tedavi konusunda kanıta dayalı tıp önerileri geliştirmektir. Anahtar Kelimeler: B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
2
0
1
Order By: Relevance
“…Several studies have reported possitive or negative association between computer use and musculosceletal symptoms ( 24 - 26 ). The prevalence of Computer Carpal Syndrome (CTS) among computer professionals based on clinical signs and sympoms is approximately 13,1% and almost 1 out of every computer professional suffers from this condition.…”
Section: Discussion and Reccomendations On Therapeutic Modalitiesmentioning
confidence: 99%
“…Several studies have reported possitive or negative association between computer use and musculosceletal symptoms ( 24 - 26 ). The prevalence of Computer Carpal Syndrome (CTS) among computer professionals based on clinical signs and sympoms is approximately 13,1% and almost 1 out of every computer professional suffers from this condition.…”
Section: Discussion and Reccomendations On Therapeutic Modalitiesmentioning
confidence: 99%
“…1,2 This discomfort, known as cervical radiculopathy, includes pain and neurological symptoms that extend from the neck into the distal extremity. [3][4][5] Traditional therapeutic exercise for patients with cervical radiculopathy has resulted in favorable outcomes; 6 however, another frequently used intervention in the treatment of patients with cervical radiculopathy is cervical traction. [3][4][5] Cervical traction has been recommended for patients who have peripheralization of symptoms with lower cervical mobility testing, positive shoulder abduction sign, positive manual distraction test, positive upper-limb tension test, and are 55 years of age or older.…”
Section: Clinical Scenariomentioning
confidence: 99%
“…26 Disk hernisine sekonder gelişen sırt ve boyun ağrılarında ozon tedavisinin ağrıyı azalttığı görülmüş olsa da gerek paravertebral gerekse intradiskal yol kullanılarak yapılan ozon enjeksiyonu ile tedavi için yüksek kaliteli randomize kontrollü çalışmalara ihtiyaç vardır. 27,28 …”
Section: Servikal Ve Lomber Ağrılarda Medikal Ozon Uygulamasıunclassified